2022
DOI: 10.1063/4.0000164
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stokes fluorescence excitation reveals conformational mobility of the C-phycocyanin chromophores

Abstract: The structural organization of natural pigment-protein complexes provides a specific environment for the chromophore groups. Yet, proteins are inherently dynamic and conformationally mobile. In this work, we demonstrate the heterogeneity of chromophores of C-phycocyanin (C-PC) from Arthrospira platensis. Part of the population of trimeric C-PC is subject to spontaneous disturbances of protein–protein interactions resulting in increased conformational mobility of the chromophores. Upon fluorescence excitation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Small-angle X-ray scattering (SAXS) measurements with SpaR proteoliposomes were performed on SAXS instrument Rigaku MicroMax-007HF at MIPT (which previously was used and was described in works 132 – 134 ) to verify the formation of ULV. A standard model of the bilayer with a symmetric step EDP function was used for description of the SAXS scattering profile for liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…Small-angle X-ray scattering (SAXS) measurements with SpaR proteoliposomes were performed on SAXS instrument Rigaku MicroMax-007HF at MIPT (which previously was used and was described in works 132 – 134 ) to verify the formation of ULV. A standard model of the bilayer with a symmetric step EDP function was used for description of the SAXS scattering profile for liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…The SAXS experiments were carried out on the Rigaku instrument at the Moscow Institute of Physics and Technology (Dolgoprudny, Russia) as described previously [47,48]. SAXS profiles were obtained for the peak fraction after gel-filtration with protein concentration of 3.5 mg/ml, in a buffer containing 150 mM NaCl and 25 mM Tris-HCl, pH 8.0.…”
Section: Small-angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…The SAXS experiments were carried out on the Rigaku instrument at the Moscow Institute of Physics and Technology (Dolgoprudny, Russia) as described previously [48,49].…”
Section: Small-angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…This is especially important when the oligomerization state of the protein complex under investigation is not known or deviates from the corresponding crystal structure. Examples include the oligomerization state of PC [68] and phycobiliproteins (PBP) from cyanobacteria [45] and the light-harvesting complexes LH1 and LH2 from purple bacteria [33] and LHCII from green plants [32].…”
Section: Structure-function Correlationmentioning
confidence: 99%
“…In the case of phycocyanin, Tsoraev et al [68] showed using SAXS that the functional unit in their spectroscopic experiments was the PC trimer. Golub et al [45] employed SANS to study PBP from Acaryochloris marina in different buffer solutions yielding different functional competence and made use of the fact that this light-harvesting complex is composed of known components: one allophycocyanin trimer (APC) and an unknown number of PC trimers.…”
Section: Structure-function Correlationmentioning
confidence: 99%